Looks straight forward to me. To "solve for C", undo everything that has been done to C, in the opposite order.
Here, calculate E=((A*(1/B-1/C)))/D*100, the last thing you would do is divide by D*100. So to "undo" that multiply by D*100. On both sides, of course. That gives 100*D*E= A*(1/B- 1/C). A is multiplying everything on the right side so get rid of it by dividing both sides by A: 100*D*E/A= 1/B- 1/C.
There is a "1/B" on the right side so subtract 1/B from both sides: 100*D*E/A- 1/B= -1/C.
Multiply both sides by -1: 1/B- 100*D*E/A= 1/C.
Now take the reciprocal of both sides:
C= 1/(1/B- 100*D*E/A)
That is the answer but you might want to simplify the right side:
Get the common denominator BA: 1/B- 100*D*E/A= A/AB- 100*D*E*B/AB= (A- 100*D*E*B)/AB
so C= AB/(A- 100*D*E*B).